Implementation of I’Adah al- Nadzar in The DSN-MUI Fatwa on Kafalah bil Ujrah - Adam Agus Putra, Panji (Fakultas Syariah IAIN madura, 2024)
The kafalah (guarantee) contract initially fell within the domain of tabarru (charitable) contracts. However, there is a difference of opinion (ikhtilaf) among scholars regarding the ruling of the kafalah bil ujrah contract (a guarantee contract accompanied by a fee). This study aims to explore the concept of I’adah al-Nadzhar and the opinions of scholars regarding the ruling of the kafalah bil ujrah contract, as well as the implementation of I’adah al-Nadzhar in DSN-MUI's fatwas. The results of the research show that the concept of I’adah al-Nadzhar is, in simple terms, a re-examination of previous scholarly opinions due to difficulties in their application, followed by adopting a new opinion, considered marjuh (weaker), as a guideline. The majority (jumhur) of scholars view the kafalah bil ujrah contract as prohibited because it resembles riba (interest). However, the National Sharia Council-Indonesian Ulema Council (DSN-MUI) permits the kafalah bil ujrah contract in several of its fatwas. Contrary to the view of the majority of Islamic jurists regarding the ruling of the kafalah bil ujrah contract, the DSN-MUI, based on the consideration of I’adah al-Nadzhar or re-examination, allows the kafalah bil ujrah contract. This is based on the reasoning that the ujrah is given for the jah (dignity/reputation) of the guarantor (kafil), the presence of hajjah (necessity), and to avoid harm (daf' al-dharar).